2019
DOI: 10.1007/164_2019_268
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Kappa-Opioid Receptors in Drug Abuse Research

Abstract: Substance use disorders represent a global public health issue. This mental health disorder is hypothesized to result from neurobiological changes as a result of chronic drug exposure and clinically manifests as inappropriate behavioral allocation towards the procurement and use of the abused substance and away from other behaviors maintained by more adaptive nondrug reinforcers (e.g. social relationships, work). The dynorphin/kappa-opioid receptor (KOR) is one receptor system that has been altered following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…Acute, non-contingent administration of U50488 or nalfurafine failed to selectively decrease fentanyl choice and decreased overall rates of operant behavior. These findings suggest KOR agonists would not be effective as standalone treatments for substance use disorders (see (Banks 2020)) and are in agreement with a report of acute enadoline treatment failing to selectively affect cocaine-versus-money choice in human volunteers (Walsh et al 2001a). Previous works have highlighted the importance of evaluating behavioral selectivity of treatment effects of candidate substance use disorder treatments (Czoty et al 2016; Haney and Spealman 2008; Mello and Negus 1996), arguing that such measures increase the potential for preclinical-to-clinical translation.…”
Section: Discussionsupporting
confidence: 87%
“…Acute, non-contingent administration of U50488 or nalfurafine failed to selectively decrease fentanyl choice and decreased overall rates of operant behavior. These findings suggest KOR agonists would not be effective as standalone treatments for substance use disorders (see (Banks 2020)) and are in agreement with a report of acute enadoline treatment failing to selectively affect cocaine-versus-money choice in human volunteers (Walsh et al 2001a). Previous works have highlighted the importance of evaluating behavioral selectivity of treatment effects of candidate substance use disorder treatments (Czoty et al 2016; Haney and Spealman 2008; Mello and Negus 1996), arguing that such measures increase the potential for preclinical-to-clinical translation.…”
Section: Discussionsupporting
confidence: 87%
“…Another explanation suggests a synergic effect of NTX and BUP. Research has suggested that the kappa opioid receptor system has a role in mood disorders (Banks, 2020;Chavkin & Koob, 2016;Crowley & Kash, 2015;Tejeda & Bonci, 2019;Wee & Koob, 2010). Studies have proposed that prolonged opioid use, and thus continued exposure to mu agonists, can result in kappa receptor system overdrive (Banks, 2020;Chavkin & Koob, 2016).…”
Section: Unblocked Effects and Pharmacological Considerationsmentioning
confidence: 99%
“…Research has suggested that the kappa opioid receptor system has a role in mood disorders (Banks, 2020;Chavkin & Koob, 2016;Crowley & Kash, 2015;Tejeda & Bonci, 2019;Wee & Koob, 2010). Studies have proposed that prolonged opioid use, and thus continued exposure to mu agonists, can result in kappa receptor system overdrive (Banks, 2020;Chavkin & Koob, 2016). This overdrive may lead to dysphoric mood states, which may be part of a prolonged abstinence reaction, symptoms which may be further increased by naltrexone mu opioid receptor blockade (Rothman, 1992;Rothman et al, 1991).…”
Section: Unblocked Effects and Pharmacological Considerationsmentioning
confidence: 99%
“…DYN is derived from pro-dynorphin (PDYN) and is the only endogenous ligand with a high affinity for KOR. Among specific KOR agonists used in preclinical research ( Banks, 2020 ), we can cite salvinorin A, the active principle of Salvia divinorum ( Roach and Shenvi, 2018 ) and the synthetic analogue U50,488 ( Karkhanis et al, 2017 ).…”
Section: The Dynorphin/kappa-opioid Receptor Systemmentioning
confidence: 99%
“…Naltrexone, as naloxone, is a non-selective mu (µ, MOR), delta (δ, DOR), and kappa (κ, KOR) opioid receptor antagonist, approved for the treatment of alcohol and opioid use disorders ( Sudakin, 2016 ), and is actually tested (in co-treatment with buprenorphine), in a phase 2 clinical trial, to treat alcohol use disorder comorbid with PTSD (NCT03852628, 2019). Interestingly, the pharmacological industry was prompted to develop KOR antagonists to treat stress-induced relapse of cocaine, alcohol, and tobacco ( Carroll and Carlezon, 2013 ; Banks, 2020 ). To our knowledge, a pharmacological strategy aiming selective KOR antagonism has not yet been explored to treat SUD/PTSD comorbidity.…”
Section: Introductionmentioning
confidence: 99%